2006
DOI: 10.1074/jbc.m603970200
|View full text |Cite
|
Sign up to set email alerts
|

Examining Interactions of HIV-1 Reverse Transcriptase with Single-stranded Template Nucleotides by Nucleoside Analog Interference

Abstract: Crystallographic studies have implicated several residues of the p66 fingers subdomain of human immunodeficiency virus type-1 reverse transcriptase in contacting the single-stranded template overhang immediately ahead of the DNA polymerase catalytic center. This interaction presumably assists in inducing the appropriate geometry on the template base for efficient and accurate incorporation of the incoming dNTP. To investigate this, we introduced nucleoside analogs either individually or in tandem into the DNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 56 publications
2
9
0
Order By: Relevance
“…By combining stopped-flow and quench-flow approaches, we demonstrated that Phe61 on p66 plays key roles in the binding of p/t by controlling the interaction between finger-thumb domains and stabilizing the 5′ overhang of the template strand, and in RT processing by stabilizing the conformation of the polymerase catalytic site. These results are along the same lines as those of previous work showing that Phe61 influences the orientation of the templating base and the geometry of the duplex, 34 and controls RT fitness and incorporation after mismatching. 32,33 Fisher et al have demonstrated that the implication of p66 Phe61 in strand displacement, DNA synthesis and RT fidelity is independent.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…By combining stopped-flow and quench-flow approaches, we demonstrated that Phe61 on p66 plays key roles in the binding of p/t by controlling the interaction between finger-thumb domains and stabilizing the 5′ overhang of the template strand, and in RT processing by stabilizing the conformation of the polymerase catalytic site. These results are along the same lines as those of previous work showing that Phe61 influences the orientation of the templating base and the geometry of the duplex, 34 and controls RT fitness and incorporation after mismatching. 32,33 Fisher et al have demonstrated that the implication of p66 Phe61 in strand displacement, DNA synthesis and RT fidelity is independent.…”
Section: Discussionsupporting
confidence: 88%
“…This result confirms the requirement of Phe61 for stabilization of the p/t in the catalytic site as previously reported. 32,34 Interestingly, similar movement of the thumb domain was observed on the structures of RT-NNRTI complexes, where the NNRTIs maintain RT in an open conformation 11,30 and improve binding of p/t in a noncatalytic conformation. 36,37 In contrast, mutation of Trp24 does not specifically affect the collisional step of the p/t binding mechanism, but alters overall kinetics, suggesting that this residue is involved in stabilization of the complex, rather than the initial RT-p/t interaction, which is not surprising, as the implication of Trp24 in the fingers-thumb domains contact in the closed conformation of RT is limited (Fig.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…They are found to play critical roles in viral DNA replication, in fidelity, and in drug resistance (Agopian et al, 2007;Dash et al, 2006;Depollier et al, 2005;Kim et al, 1998Kim et al, , 1999.…”
Section: Discussionmentioning
confidence: 99%